2021
DOI: 10.1111/cge.13939
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in adults with osteogenesis imperfecta

Abstract: Patient-reported outcome measures (PROMs) are increasingly utilized as endpoints in clinical trials. The Short Form Health Survey-12 (SF-12v2) is a generic PROM for adults. We sought to evaluate the validity of SF-12v2 in adults with osteogenesis imperfecta (OI). Physical and mental health-related quality of life (HRQoL) were assessed in a large cohort of adults in a multicenter, observational, natural history study. Physical HRQoL scores were correlated with the Gillette Functional Assessment Questionnaire (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…However, in contrast to this classification, we found that the prevalence of chronic pain in the entire sample and the degree of pain interference in adults were similar across OI types. This finding agrees with previous publications, where pain intensity and bodily pain did not correlate with the severity of the disease (Arponen et al, 2018;Murali et al, 2021;Smith, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in contrast to this classification, we found that the prevalence of chronic pain in the entire sample and the degree of pain interference in adults were similar across OI types. This finding agrees with previous publications, where pain intensity and bodily pain did not correlate with the severity of the disease (Arponen et al, 2018;Murali et al, 2021;Smith, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…To comprehensively understand the pain in OI, we also analyzed the pain content of questions we considered substantially related to pain from PODCI in children and the SF‐12v2 in adults (Table 1). The global scores of these two questionnaires by OI type have already been published (Murali et al, 2020; Murali et al, 2021). Additionally, all the participants were asked if they were under active IV BPs treatment (yes or no).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, physical HR-QOL was most impaired in those diagnosed with type 3 OI. Four studies in this review reported signi cantly lower PCS scores in patients living with type 3 compared with type 1 OI (26,27,30,31) . A study by Yonko et al also reported lower respiratory-related QOL in patients living with type 3 compared with type 1 OI.…”
Section: Impact Of Oi Type On Hr-qolmentioning
confidence: 80%
“…In addition, one study reported physical but not mental domains of the SF-36 (30) and another used an abbreviated version called the SF-12 (31) . There was signi cant heterogeneity in how the results of the SF-36 were reported.…”
Section: Hr-qol Assessment Usedmentioning
confidence: 99%